“You shouldn’t have to suffer for being who you are”: An examination of the Human Library strategy for challenging prejudice and increasing respect for difference - Watson, Gregory John (Curtin University, 2015)
This qualitative research examines the Human Library method of engaging people in dialogue to challenge prejudice and increase respect for difference and human rights. Its data, collected via participant-observation and 44 semi in-depth interviews with Human Library participants, are interpreted using constructivist grounded theory. The research concludes that Human Libraries are spaces for rights and freedoms that engage people in three process concepts: raising critical consciousness, human recognition and enabling human rights activism.